Dari Bangsal menuju Pergaulan Global: Perubahan Identitas Orang Maluku di Belanda - Hatib Abdul Kadir (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2012)
This paper describes the process of change in post-colonial migrants in the Netherlands such as identity, parenting, community, solidarity, weddings and fashion sense of nationhood that is constantly changing between generations. This paper is evolutionary, which saw communities that were initially confined in a room (ward) and nationalism without a nation in transition, which is a community that feels himself entirely at once instead of Dutch Moluccans. At the end of the third generation and beyond Maluku generation undergo a process of identity change in a more open and responsive to global changes. The question this paper as the background for what the process of identity change occurred? How people articulate their identity as Maluku migrant communities? how they maintain a sense of brotherhood with the people of Maluku in Indonesia and how the relationship with indigenous people and other migrants? The purpose of this paper is to find a model of learning the identity of political negotiations among the minorities, the learning of citizenship in a state and show that the formation of identity as an unstable between generations.Keywords: transformation of identity, intergenerational change, immigrant, minority